Preparation method of hard carbon microspheres with high graphitization degree
By using the metal salt of organic iron acid-based element as catalyst and precursor, combined with hydrothermal and constant temperature carbonization technology, the degree of graphitization of hard carbon microspheres has been successfully improved, and the problems of low graphitization and uneven distribution of catalysts in the existing technology have been solved, and the preparation of hard carbon microspheres with high graphitization has been achieved, with good application prospects.
Patent Information
- Application Number
- CN202411742502.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-28
AI Technical Summary
The prior art is difficult to effectively improve the degree of graphitization on the basis of maintaining the original advantages of hard carbon microspheres, and external graphitization catalysts are often required, resulting in uneven catalyst distribution and damage to the surface structure.
The metal salt of iron-based organic acid element is used as the transition metal salt of the hard carbon precursor and catalyst, and hard carbon microspheres with high graphitization degree are prepared through two steps of hydrothermal carbonization and constant temperature carbonization. This method realizes uniform graphitization of hard carbon microspheres by controlling temperature and solubility, reducing the damage to the surface of the microspheres during catalysis.
It has achieved high graphitization degree and uniformity of hard carbon microspheres, unified particle size, good dispersion and fluidity, and is suitable for energy storage, catalysis, refractory materials and other fields.
Smart Images

Figure CN119706822A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of carbon material preparation, and in particular relates to a method for preparing hard carbon microspheres with a high graphitization degree. Background Art
[0002] As a zero-dimensional material with large specific surface area, high bulk density, high fluidity and excellent chemical stability, hard carbon microspheres have attracted wide attention in many fields. Among them, hard carbon microspheres with high graphitization degree have higher electrical conductivity, thermal conductivity and mechanical strength due to their high graphitization degree and obvious graphite sheet structure, and have more advantages in practical applications in energy storage, catalysis, refractory materials, adsorption and other fields.
[0003] At present, the preparation methods of hard carbon microspheres with high graphitization degree mainly include high temperature and high pressure method, emulsification method, chemical activation method, and thermal polycondensation method. These preparation methods have problems such as complex process, high energy consumption, and high cost to varying degrees, making it difficult to achieve large-scale production and application. The hydrothermal carbonization method often uses monosaccharides or polysaccharides such as glucose, fructose, cellulose, starch, and biomass derivatives as carbon precursors, and uses colloid and polymer scientific methods to regulate the structure and morphology of carbon products. Its carbonization products are generated under relatively mild conditions and will not destroy the physical properties of the products. Most of them are good spherical structures. Because of its simple preparation process, low cost, good dispersion of prepared carbon balls, and uniform particle size, it is the most commonly used method for preparing carbon microspheres. Most of the hard carbon microspheres prepared by hydrothermal carbonization are amorphous structures with low graphitization degree. Since hard carbon is still difficult to graphitize at high temperature, the effect of high temperature carbonization on improving the graphitization of hard carbon is relatively limited. At present, in order to obtain hard carbon microspheres with high graphitization degree, external graphitization catalysts (such as iron, cobalt, nickel, etc.) are usually introduced to improve the graphitization degree of hard carbon microspheres. For example, the patent application number CN201710195233.5 reported "a sodium ion battery carbon ball negative electrode material and its preparation method", which prepared carbon balls by hydrothermal glucose, immersed them in a cobalt salt solution, and then carbonized at a constant temperature of about 1000 ° C to obtain a concentric spherical carbon material with an inner layer of hard carbon and an outer layer of graphitized carbon material layer. Patent application number CN201810776624.0 reports "a method for preparing hemicellulose-based graphitized porous carbon microspheres and their application", in which carbon microspheres are prepared by hot water hemicellulose, and then iron salts are introduced during high-temperature carbonization to obtain graphitized porous carbon microspheres. The method of increasing the degree of graphitization of materials by introducing external graphitization catalysts usually makes it difficult to ensure uniform distribution of the catalyst and consistency of the degree of graphitization, and the surface structure of the hard carbon microspheres may be destroyed during the catalytic process.
[0004] Therefore, how to improve the graphitization degree of hard carbon microspheres by effective means while maintaining the original advantages is an urgent problem to be solved in current research. Exploring new preparation technologies for highly graphitized hard carbon microspheres is not only of great significance to the development of materials science, but also has practical value in promoting technological progress in related industries. Summary of the invention
[0005] To solve the above problems, the present invention provides a simple, easy and low-cost method for preparing hard carbon microspheres with a high degree of graphitization. The prepared hard carbon microspheres have uniform particle size, good spherical shape, high and uniform degree of graphitization.
[0006] The technical solution adopted by the present invention is as follows:
[0007] In a first aspect, the present invention provides a method for preparing hard carbon microspheres with a high degree of graphitization, which specifically comprises the following steps:
[0008] Step 1: dissolving an organic acid iron-based metal salt or a mixture of an organic acid iron-based metal salt and an organic substance in water to prepare an aqueous solution;
[0009] The mixture of the organic acid iron element metal salt and organic matter comprises: the organic acid iron element metal salt and any one of the organic acid, organic alcohol, organic aldehyde or organic aldehyde polymer of the organic acid iron element metal salt, and the molar ratio of the two is 1:1 to 1:20;
[0010] Metal salts of organic acid iron elements are used as transition metal salts of hard carbon precursors and catalysts;
[0011] Step 2: Hydrothermally carbonize the aqueous solution prepared in step 1 at 100-180° C. for 4-12 hours, and filter and dry the obtained hydrothermal product;
[0012] Step 3, placing the hydrothermal product in an inert gas and carbonizing at a constant temperature of 800 to 1200° C. for 1 to 2 hours;
[0013] Step 4, cooling the solid reaction product in step 3, taking it out, dissolving and washing it with a 0.1-1.0 mol / L acid solution to remove residual inorganic salts, and finally repeatedly washing it with pure water until it becomes neutral to obtain hard carbon microspheres with a high degree of graphitization.
[0014] Preferably, the organic acid iron-based metal salt is gluconate, citrate or lignin sulfonate.
[0015] Furthermore, the gluconate is any one of iron gluconate, cobalt gluconate, and nickel gluconate, or a mixture of two or more thereof;
[0016] The organic matter that can be mixed with gluconate is any one of monosaccharide, disaccharide and polysaccharide or a mixture of two or more thereof.
[0017] Furthermore, the monosaccharides include glucose, fructose, and galactose; the disaccharides include sucrose, lactose, maltose, and cellobiose; and the polysaccharides include starch, cellulose, glycogen, and pectin.
[0018] Furthermore, the citrate is any one of ferric citrate, nickel citrate, and cobalt citrate, or a mixture of two or more thereof, and is mixed with citric acid.
[0019] Furthermore, the lignin sulfonate is any one of iron lignin sulfonate, cobalt lignin sulfonate, and nickel lignin sulfonate, or a mixture of two or more thereof, and is mixed with lignin;
[0020] The organic matter that can be mixed with lignin sulfonate is lignin.
[0021] Preferably, the mass concentration of the aqueous solution prepared in step 1 is 30-150 mg / mL.
[0022] Preferably, the inert gas in step three is nitrogen, argon or a mixture of the two.
[0023] Preferably, the acid solution used in step 4 is one or a mixture of two or more of hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid and acetic acid.
[0024] In a second aspect, the present invention provides hard carbon microspheres with a high degree of graphitization, which are prepared by the method described in the first aspect.
[0025] The beneficial effects of the present invention are as follows: (1) The present invention utilizes the characteristic that organic acid salts are easily cross-linked into balls during a hydrothermal process, and can prepare hard carbon microspheres of different particle sizes by controlling temperature and solubility. In the subsequent constant temperature carbonization process, since salt ions are uniformly dispersed in the organic acid salts at the atomic level, the metal inorganic salts produced by pyrolysis can be more uniformly present in the carbon microspheres, thereby achieving a uniform graphitization catalytic effect, ensuring the consistency of the graphitization degree of the hard carbon microspheres, and effectively reducing the damage to the surface of the hard carbon microspheres during the catalytic process.
[0026] (2) This method has low equipment requirements, simple process, and is easy to implement in large-scale production.
[0027] (3) The highly graphitized hard carbon microspheres prepared by this method have uniform particle size, good dispersibility and fluidity, high degree of graphitization and good consistency, and can have good practical applicability in many fields such as energy storage, catalysis, refractory materials, adsorption, and biomedicine. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1This is a SEM image of hard carbon microspheres with a high degree of graphitization prepared in Example 2 of the present invention;
[0029] Figure 2 TEM image of hard carbon microspheres with high graphitization degree prepared in Example 2 of the present invention;
[0030] Figure 3 This is a Raman graph of hard carbon microspheres with a high degree of graphitization prepared in Example 2 of the present invention;
[0031] Figure 4 This is the XRD diagram of the hard carbon microspheres with a high degree of graphitization prepared in Example 2 of the present invention. DETAILED DESCRIPTION
[0032] The present invention is further described below in conjunction with the accompanying drawings and embodiments. The present invention includes but is not limited to the following embodiments.
[0033] Example 1
[0034] Ferric gluconate was dissolved in deionized water to prepare a solution with a mass solubility of 50 mg / mL, and hydrothermaled at 160°C for 8 hours. The obtained product was filtered and dried to obtain raw material microspheres. The raw material microspheres were heated to 1000°C at a heating rate of 5°C / min under argon protection, and carbonized at this temperature for 2 hours. After cooling, they were dissolved and washed with 1 mol / L hydrochloric acid solution to remove residual impurities, and finally washed repeatedly with pure water until neutral, to obtain hard carbon microspheres with a diameter of about 6 microns and a high degree of graphitization.
[0035] Example 2
[0036] Ferric gluconate and glucose were mixed in a molar ratio of 1:1, dissolved in deionized water, and prepared into a solution with a mass solubility of 75 mg / mL. The solution was hydrothermally heated at 160°C for 12 hours, and the obtained product was filtered and dried to obtain raw material microspheres. The raw material microspheres were heated to 1000°C at a heating rate of 5°C / min under argon protection, and carbonized at this temperature for 2 hours. After cooling, they were dissolved and washed with 1 mol / L hydrochloric acid solution to remove residual impurities, and finally washed repeatedly with pure water until neutral. SEM showed that the material was a carbon sphere with a complete spherical shape and a diameter of about 10 microns; TEM showed that an ordered graphite microcrystalline structure appeared in most areas, with an interlayer spacing of 0.34nm and a relatively uniform degree of graphitization; XRD showed a sharp (002) crystal plane diffraction peak at 26o and a typical characteristic peak (2D peak) of graphene in the Raman spectrum, indicating that the synthesized carbon spheres had a high degree of graphitization.
[0037] Example 3
[0038] Nickel gluconate and fructose were mixed in a molar ratio of 1:20, dissolved in deionized water to prepare a solution with a mass solubility of 75 mg / mL, and hydrothermaled at 160°C for 4 hours. The obtained product was filtered and dried to obtain raw material microspheres; the raw material microspheres were heated to 1000°C at a heating rate of 5°C / min under argon protection, and carbonized at this temperature for 2 hours. After cooling, they were dissolved and washed with 1 mol / L hydrochloric acid solution to remove residual impurities, and finally washed repeatedly with pure water until neutral, to obtain hard carbon microspheres with a diameter of about 6 microns and a high degree of graphitization.
[0039] Example 4
[0040] Cobalt gluconate and starch are mixed in a molar ratio of 1:10, dissolved in deionized water to prepare a solution with a mass solubility of 100 mg / mL, and hydrothermally heated at 100°C for 6 hours. The obtained product is filtered and dried to obtain raw material microspheres; the raw material microspheres are heated to 1000°C at a heating rate of 5°C / min under argon protection, and carbonized at this temperature for 2 hours. After cooling, they are dissolved and washed with 1 mol / L hydrochloric acid solution to remove residual impurities, and finally repeatedly washed with pure water until neutral, to obtain hard carbon microspheres with a diameter of about 6 microns and a high degree of graphitization.
[0041] Example 5
[0042] Nickel gluconate and glucose were mixed in a molar ratio of 1:3, dissolved in deionized water to prepare a solution with a mass solubility of 150 mg / mL, and hydrothermally heated at 180°C for 6 hours. The obtained product was filtered and dried to obtain raw material microspheres; the raw material microspheres were heated to 800°C at a heating rate of 5°C / min under argon protection, and carbonized at this temperature for 2 hours. After cooling, they were dissolved and washed with 1 mol / L hydrochloric acid solution to remove residual impurities, and finally washed repeatedly with pure water until neutral, to obtain hard carbon microspheres with a diameter of about 12 microns and a high degree of graphitization.
[0043] Example 6
[0044] Ferric citrate and citric acid are mixed in a molar ratio of 1:1, dissolved in deionized water to prepare a solution with a mass solubility of 50 mg / mL, and hydrothermally heated at 180°C for 8 hours. The obtained product is filtered and dried to obtain raw material microspheres; the raw material microspheres are heated to 1000°C at a heating rate of 5°C / min under argon protection, and carbonized at this temperature for 2 hours. After cooling, they are dissolved and washed with 1 mol / L hydrochloric acid solution to remove residual impurities, and finally repeatedly washed with pure water until neutral, to obtain hard carbon microspheres with a diameter of about 8 microns and a high degree of graphitization.
[0045] Example 7
[0046] Nickel lignin sulfonate and lignin were mixed in a molar ratio of 1:10, dissolved in deionized water to prepare a solution with a mass solubility of 50 mg / mL, and hydrothermally heated at 140°C for 8 hours. The obtained product was filtered and dried to obtain raw material microspheres; the raw material microspheres were heated to 1200°C at a heating rate of 5°C / min under argon protection, and carbonized at this temperature for 2 hours. After cooling, they were dissolved and washed with 1 mol / L hydrochloric acid solution to remove residual impurities, and finally washed repeatedly with pure water until neutral, to obtain hard carbon microspheres with a diameter of about 10 microns and a high degree of graphitization.
[0047] The above contents are only basic descriptions of the concept of the present invention, and any equivalent changes made according to the technical solution of the present invention shall fall within the protection scope of the present invention.
Claims
1. A method for preparing hard carbon microspheres with a high degree of graphitization, characterized in that: The specific steps are as follows: Step 1: dissolving an organic acid iron-based metal salt or a mixture of an organic acid iron-based metal salt and an organic substance in water to prepare an aqueous solution; The mixture of the organic acid iron element metal salt and organic matter comprises: the organic acid iron element metal salt and any one of the organic acid, organic alcohol, organic aldehyde or organic aldehyde polymer of the organic acid iron element metal salt, and the molar ratio of the two is 1:1 to 1:20; Step 2: Hydrothermally carbonize the aqueous solution prepared in step 1 at 100-180° C. for 4-12 hours, and filter and dry the obtained hydrothermal product; Step 3, placing the hydrothermal product in an inert gas and carbonizing at a constant temperature of 800 to 1200° C. for 1 to 2 hours; Step 4, cooling the solid reaction product in step 3, taking it out, dissolving and washing it with a 0.1-1.0 mol / L acid solution to remove residual inorganic salts, and finally repeatedly washing it with pure water until it becomes neutral to obtain hard carbon microspheres with a high degree of graphitization.
2. The method for preparing hard carbon microspheres with a high degree of graphitization according to claim 1, characterized in that: The organic acid iron-based metal salt is gluconate, citrate or lignin sulfonate.
3. The method for preparing hard carbon microspheres with a high degree of graphitization according to claim 2, characterized in that: The gluconate is any one of ferric gluconate, cobalt gluconate and nickel gluconate or a mixture of two or more thereof; the organic matter mixed with the gluconate is any one of monosaccharide, disaccharide and polysaccharide or a mixture of two or more thereof.
4. The method for preparing hard carbon microspheres with a high degree of graphitization according to claim 3, characterized in that: The monosaccharides include glucose, fructose, and galactose; the disaccharides include sucrose, lactose, maltose, and cellobiose; and the polysaccharides include starch, cellulose, glycogen, and pectin.
5. The method for preparing hard carbon microspheres with a high degree of graphitization according to claim 2, characterized in that: The citrate is any one of ferric citrate, nickel citrate and cobalt citrate or a mixture of two or more thereof; the organic matter mixed with the citrate is citric acid.
6. The method for preparing hard carbon microspheres with a high degree of graphitization according to claim 2, characterized in that: The lignin sulfonate is any one of iron lignin sulfonate, cobalt lignin sulfonate and nickel lignin sulfonate or a mixture of two or more thereof; the organic matter mixed with the lignin sulfonate is lignin.
7. The method for preparing hard carbon microspheres with a high degree of graphitization according to claim 1, characterized in that: The mass concentration of the aqueous solution prepared in step 1 is 30-150 mg / mL.
8. The method for preparing hard carbon microspheres with a high graphitization degree according to claim 1, characterized in that: In step 3, the inert gas is nitrogen, argon or a mixture of the two.
9. The method for preparing hard carbon microspheres with a high degree of graphitization according to claim 1, characterized in that: The acid solution used in step 4 is one or a mixture of two or more of hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid and acetic acid.
10. Hard carbon microspheres with a high degree of graphitization, prepared by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
A carbon ball anode material for sodium-ion batteries and its preparation method
CN106910880B
Preparation method and application of hemicellulose based graphitized porous carbon microsphere
CN108751183A